Blueprint : Adjustable Fruit Opener / Ahmad Nur’alif Mohamad Nadzir - Mohamad Nadzir, Ahmad Nur’alif (2020)
Adjustable Fruit Opener will provide them solutions in order to satisfy their needs and to solve their problems. The idea of this design of fruit opener is simply from already existed in the market. The function of existed product is only to open the durian. For this Adjustable Fruit Opener, it has two functions. This product has an additional special feature with a cylindrical carbon steel. The used of this component is to get coconut water out of a coconut. So, the user can use it and enjoy the coconut water as a refreshing and hydrating beverage while waiting the coconut to open. The other function of this product is to open the king of fruit known as durian. This is due to the problem that durian has a parabolic shape and it surface is thorny. It also can be used to open the coconut because the coconut has hard surface. By using this adjustable fruit opener, the user can make their job easier and more enjoy. The best part of this product is it is suit to anybody that has zero skill to open the fruit. The advantage of the product is to reduce the probability of the user’s hand getting hurt and taking short time for the process.